Average American teenager? White working-class high school students navigate race, privilege and opportunity. - Freie, Carrie (Social Identities)
Using findings from an interview-based ethnographic research study, this article explores the social identity development of white suburban high school students in a working-class area of north-eastern United States. Discussion focuses on the ways that ‘whiteness’ and ‘normality’ become conflated for these white working-class teens as they identify themselves as ‘average,’ ‘regular,’ and ‘normal,’ by enlisting neoliberal discourses of individuality, consumerism, and opportunity. I argue that these discourses of normality work to hide both the white privilege as well as the disadvantages the teens experience as a result of their working-class backgrounds.